2008
DOI: 10.1007/s11664-008-0403-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress–Strain Characteristics of Tin-Based Solder Alloys for Drop-Impact Modeling

Abstract: The stress-strain properties of eutectic Sn-Pb and lead-free solders at strain rates between 0.1 s -1 and 300 s -1 are required to support finite-element modeling of the solder joints during board-level mechanical shock and productlevel drop-impact testing. However, there is very limited data in this range because this is beyond the limit of conventional mechanical testing and below the limit of the split Hopkinson pressure bar test method. In this paper, a specialized drop-weight test was developed and, toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…Many studies have shown that Young's modulus can be assumed to be independent of strain rate from quasi-static to very high strain rates (up to 300 s À1 ) [9,[36][37][38][39][40]. The present FEM showed that this was particularly true for the calculation of J ci , which decreased by only 2% when the solder Young's modulus was increased from 51 GPa to 110 GPa.…”
Section: Finite Element Modelingmentioning
confidence: 50%
See 1 more Smart Citation
“…Many studies have shown that Young's modulus can be assumed to be independent of strain rate from quasi-static to very high strain rates (up to 300 s À1 ) [9,[36][37][38][39][40]. The present FEM showed that this was particularly true for the calculation of J ci , which decreased by only 2% when the solder Young's modulus was increased from 51 GPa to 110 GPa.…”
Section: Finite Element Modelingmentioning
confidence: 50%
“…[23,[30][31][32][33]. Table 2 lists the values that were used, taken from the SAC305 properties provided in [34,35] and the stress-strain curves of [36]. Linear interpolation was used to estimate the yield stress at strain rates where the yield stress at the corresponding strain rate was not reported directly.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Since the solder yield stress is a function of strain rate [20,[34][35][36][37], the SAC305 properties were defined using the data of [38,39] and the stress-strain curves of [40] as shown in Table 1. The Young's modulus and Poisson's ratio of SAC305 were assumed to be, respectively, 51 GPa and 0.4, while those for the copper were taken to be 124 GPa and 0.35 [38,39].…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…The higher susceptibility to brittle fracture is because the flow stress of the bulk solders increases with strain rate, 14 while the dynamic fracture toughness of the brittle intermetallic compound (IMC) tends to decrease with increasing strain rate. 15 It is well known that the fracture toughness of a structure is a function of the size and distribution of the defects within the structure.…”
Section: Resultsmentioning
confidence: 99%
“…12, where the flow stress was characterized at 0.1 strain at strain rate of 50 s -1 (Table V). 14 The following observations were made: (i) BLDST-life decreased with increased flow stress of the solder alloys, (ii) the OSP pad finish outperformed the ENIG pad finish in general (more so for solder alloys of lower flow stress), but both finishes displayed similar sensitivity towards the flow stress of the solder alloy-a 100% increase in the flow stress of the solder alloy resulted in approximately 50% reduction in BLDST-life, (iii) High-Speed Cyclic Bend Tests and Board-Level Drop Tests for Evaluating the Robustness of Solder Joints in Printed Circuit Board Assemblies doping the solder alloys with minute amount of Ni increased the BLDST-life in general, but the effects varied-doping was much more effective for OSP than for ENIG pad finish; it was much more effective for SAC101 than for SAC305 solder; and doping has no effect at all for the SAC305_ENIG solder joint.…”
Section: Board-level Drop-shock Testmentioning
confidence: 99%